SLA-driven flexible bandwidth reservation negotiation schemes for QoS aware IP networks - Chieng, David; Parr, Gerard; Marshall, Alan (Springer Berlin Heidelberg, 2004)
We present a generic Service Level Agreement (SLA)-driven service provisioning architecture, which enables dynamic and flexible bandwidth reservation schemes on a per-user or a per-application basis. Various session level SLA negotiation schemes involving bandwidth allocation, service start time and service duration parameters are introduced and analysed. The results show that these negotiation schemes can be utilised for the benefits of both end user and network provide such as getting the highest individual SLA optimisation in terms of Quality of Service (QoS) and price. A prototype based on an industrial agent platform has also been built to demonstrate the negotiation scenario and this is presented and discussed.